Enhancing the Bioavailability and Efficacy of Vismodegib for the Control of Skin Cancer: In Vitro and In Vivo Studies - Heba F. Salem; Amr Gamal; Haitham Saeed; Marwa Kamal; Alaa S. Tulbah (Pharmaceuticals, 2022)
Skin cancer is the most frequent cancer throughout the world. Vismodegib (VSD) is a hedgehog blocker approved for the prevention and treatment of skin cancer. VSD, however, is poorly bioavailable and has been linked to side effects. This work focused on designing a nano-invasome gel as a vehicle for enhancing the permeation, bioavailability, and efficacy of VSD. Additionally, the combined effect of terpenes and ethanol was studied on the permeation of VSD compared with liposomes. The prepared VSD-loaded invasomes (VLI) formulation included cineole (1%v/v), cholesterol (0.15%w/w), phospholipid (2%w/w), and ethanol (3%v/v) and displayed an entrapment efficiency of 87.73 ± 3.82%, a vesicle size of 188.27 ± 3.25 nm, and a steady-state flux of 9.83 ± 0.11 µg/cm2/h. The VLI formulation was vigorously stirred into a carbopol base before being characterized in vivo to investigate the permeation, bioavailability, and efficacy of VSD. The VLI gel enhanced the dermal permeation of VSD and, as a result, had 3.59 times higher bioavailability with excellent antitumor action as compared to oral VSD. In summary, as an alternative to oral administration for skin cancer treatment, invasomes are efficient carriers for delivering VSD and enhancing its transdermal flux into deep skin layers.